Group Reminiscence Therapy for Dementia to Improve Well-Being and Reduce Behavioral Symptoms - Yanagida, Nobuhiko; Yamaguchi, Takumi; Matsunari, Yuko (Geriatrics, 2024)
The global increase in dementia cases highlights the urgent need for effective treatment and care strategies. The aim of this study was to evaluate the effects of group reminiscence therapy on cognitive function, subjective well-being, and behavioral and psychological symptoms of dementia (BPSD) in older adults with moderate to severe dementia. A pre–post comparative design was used, with 49 participants receiving eight group reminiscence therapy sessions over 4 weeks. Baseline, one-week, and one-month postintervention assessments were conducted using the Hasegawa Dementia Scale-Revised (HDS-R), the Neuropsychiatric Inventory-Nursing Home Version (NPI-NH), and the Philadelphia Geriatric Center Morale Scale (PGC Morale Scale). The results showed no significant improvement in HDS-R scores, but significant improvements in PGC Morale Scale (p = 0.0417) and NPI-NH scores (p = 0.00226), indicating improved well-being and reduced BPSD. These findings suggest that group reminiscence therapy is effective in improving BPSD. Future research should focus on extending the duration of the intervention, including different populations, and combining group reminiscence therapy with other therapeutic approaches to fully determine its long-term benefits and mechanisms. Research on its cost-effectiveness and cultural applicability could further validate and improve the use of group reminiscence therapy in diverse care settings.